Comparative Analysis of BTK Inhibitors and Mechanisms Underlying Adverse Effects - Estupiñán, H. Yesid; Berglöf, Anna; Zain, Rula; Smith, C. I. Edvard (Frontiers in Cell and Developmental Biology, 2021)
The cytoplasmic protein-tyrosine kinase BTK plays an essential role for differentiation and survival of B-lineage cells and, hence, represents a suitable drug target. The number of BTK inhibitors (BTKis) in the clinic has increased considerably and currently amounts to at least 22. First-in-class was ibrutinib, an irreversible binder forming a covalent bond to a cysteine in the catalytic region of the kinase, for which we have identified 228 active trials listed at ClinicalTrials.gov. Next-generation inhibitors, acalabrutinib and zanubrutinib, are approved both in the US and in Europe, and zanubrutinib also in China, while tirabrutinib is currently only registered in Japan. In most cases, these compounds have been used for the treatment of B-lymphocyte tumors. However, an increasing number of trials instead addresses autoimmunity and inflammation in multiple sclerosis, rheumatoid arthritis, pemphigus and systemic lupus erythematosus with the use of either irreversibly binding inhibitors, e.g. evobrutinib and tolebrutinib, or reversibly binding inhibitors, like fenebrutinib. Adverse effects (AEs) have predominantly implicated inhibition of other kinases with a BTKi-binding cysteine in their catalytic domain. Analysis of the reported AEs suggests that ibrutinib-associated atrial fibrillation is caused by binding to ERBB2/HER2 and ERBB4/HER4. However, the binding pattern of BTKis to various additional kinases does not correlate with the common assumption that skin manifestations and diarrhoeas are off-target effects related to EGF receptor inhibition. Moreover, dermatological toxicities, diarrhoea, bleedings and invasive fungal infections often develop early after BTKi treatment initiation and subsequently subside. Conversely, cardiovascular AEs, like hypertension and various forms of heart disease, often persist